Frequency of Diabetes and Prediabetes in Heart Failure Patients and Their Association with In-Hospital Outcome (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Background: There are an increasing number of hospital admissions due to heart failure with diabetes or prediabetes in different hospitals in Bangladesh. But very little is known about the frequency of diabetes and prediabetes and the effect of its presence on the characteristics and outcome in patients hospitalized for heart failure. The objective of this study was to find out the frequency of diabetes and prediabetes in heart failure patients and to assess their association with in-hospital outcome.Methods: This cross sectional analytical study was done in the department of Biochemistry and Cardiology of Bangabandhu Sheikh Mujib Medical University in collaboration with department of Cardiology of National Institute of Cardiovascular Diseases, and Dhaka Medical College Hospital from July 2010 to June 2011. After proper ethical consideration a total two hundred and fifty heart failure patients were enrolled in the study by nonrandom sampling. Fasting blood sugar was done in all patients and oral glucose tolerance test was done in patients with impaired fasting glycaemia. Results: The frequency of prediabetes among the total population was 12.8% (95% CI, 8.7-16.8) and that of diabetes was 37.2% (95% CI, 31.2-43.2%). Improvement was achieved in 27 (84.4%) cases in prediabetic group, 75 (80.6%) cases in diabetic group and 105 (84.0%) cases in nondiabetic group. Mortality rates in prediabetes, diabetes and nondiabetes were 5 (15.6%); 18 (19.4%) and 20 (16.0%) respectively. The differences found among the three groups were not statistically significant (p>0.05). Length of hospital stay was also similar in all groups of study subjects. Conclusion: Frequency of diabetes among heart failure patients is high and pre-diabetes is not negligible in our country. Future studies in this field should focus on all types of glucose abnormalities rather than previously diagnosed diabetes only.DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i1.19409